2022
DOI: 10.3390/diseases10010013
|View full text |Cite
|
Sign up to set email alerts
|

Acute Demyelinating Encephalomyelitis Post-COVID-19 Vaccination: A Case Report and Literature Review

Abstract: New advancements in the medical community have rapidly occurred with the development of medical information across the globe during the COVID-19 pandemic. Several vaccine manufacturers were able to obtain clearance to administer vaccines in selected age groups and for those at high risk for COVID-19 complications. As vaccines became more readily available, there was a significant effort supported by scientific information to get people vaccinated to boost herd immunity. Acute demyelinating encephalomyelitis (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…We also summarize case reports of COVID‐19 vaccine‐related encephalomyelitis in Table 4 . 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Similar to our case, the symptoms of encephalitis developed within 30 days after vaccination. After excluding alternative causes, vaccination‐related autoimmune encephalitis was suspected and symptoms rapidly recovered after the initiation of immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also summarize case reports of COVID‐19 vaccine‐related encephalomyelitis in Table 4 . 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Similar to our case, the symptoms of encephalitis developed within 30 days after vaccination. After excluding alternative causes, vaccination‐related autoimmune encephalitis was suspected and symptoms rapidly recovered after the initiation of immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 87%
“…Zuhorn et al 18 also reported 3 cases of acute encephalitis after AZ vaccine injection. We also summarize case reports of COVID‐19 vaccine‐related encephalomyelitis in Table 4 8,19–26 . Similar to our case, the symptoms of encephalitis developed within 30 days after vaccination.…”
Section: Discussionsupporting
confidence: 75%
“…Overall, we have identified 17 previous case reports of patients with ADEM following SARS-CoV-2 vaccination, including vaccines based on mRNA, viral vector and inactivated virus (Kania et al 2021 ; Vogrig et al 2021 ; Shimizu et al 2021 ; Lee et al 2022 ; Poli et al 2022 ; Ahmad et al 2022 ; Maramattom et al 2022 ; Rinaldi et al 2022 ; Permezel et al 2022 ; Mumoli et al 2022 ; Nagaratnam et al 2022 ; Al-Quliti et al 2022 ; Lazaro et al 2022 ; Garg et al 2022 ; Cao and Ren 2022 ; Ozgen Kenangil et al 2021 ; Yazdanpanah et al 2022 ); however, this case report is the first described case of ADEM following exposure to the Ad26.COV2.S vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…We have been able to identify 17 case reports that have described ADEM, including one case report of ADEM-like presentation, following a COVID-19 vaccination: seven cases with mRNA vaccine (from Moderna and Pfizer), (Kania et al 2021 ; Vogrig et al 2021 ; Shimizu et al 2021 ; Lee et al 2022 ; Poli et al 2022 ; Ahmad et al 2022 ; Maramattom et al 2022 ) seven cases with a viral vector vaccine (from AstraZenica and Sputnik V) (Rinaldi et al 2022 ; Permezel et al 2022 ; Mumoli et al 2022 ; Nagaratnam et al 2022 ; Al-Quliti et al 2022 ; Lazaro et al 2022 ; Garg et al 2022 ) and three cases with vaccines based on inactivated virus (from SinoVac and Sinopharm) (Cao and Ren 2022 ; Ozgen Kenangil et al 2021 ; Yazdanpanah et al 2022 ). However, this case report is the first described case of ADEM following exposure to the Ad26.COV2.S vaccine from Johnson & Johnson.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the SARS-CoV-2 vaccine and ADEM literature showed 13 reported cases of ADEM following the administration of a COVID-19 vaccine, which are summarized in Table 2 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%